PELATIHAN PUBLIC SPEAKING UNTUK ANAK ASUH DI LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) MUHAMMADIYAH BUDI MULIA SUMBERSARI KABUPATEN JEMBER - sudahri, sudahri; Agustina, Lady; hadi, syamsul (FKIP Universitas Wisnuwardhana, 2024)
Every individual in society and in society is definitely faced with a situation where he or she has to speak in public (public speaking). Many people when speaking in public experience tremendous psychological pressure, feeling very nervous, nervous, not confident and so on. To be able to speak well in public, special skills and maximum preparation are needed, including mastery of the stage, mastery of the material to be presented, good use of language, appropriate use of body language, voice intonation, facial expressions, vocal training and so on..The Muhammadiyah Budi Mulia Child Welfare Institution (LKSA) Jember Regency has at least 30 foster children living at various levels of education from elementary school to university. The foster children at LKSA are busy every day with routine activities such as formal school, joining organizations and within the LKSA itself, foster children are also required to take part in pre-programmed diniyah activities. There are several activities that require foster children to be proficient in public speaking, including the participation of foster children in various student organization activities, one of the programs of which is public speaking, including scientific orations, lectures and cults. These various activities are an obligation for all foster children to participate in. It is not uncommon for LKSA children to experience difficulties in transforming the message that must be conveyed. They looked very nervous, not confident, some of the foster children even stammered and even stopped talking